PERAN PENTING KOMPETENSI GURU DALAM KEGIATAN BELAJAR MENGAJAR DI SD N GUWOSARI - Nenni Aprilia Ningsih; Henry Aditia Rigianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Teachers act as role models and central figures for their students. Meanwhile, the wave of globalization is rapidly spreading, particularly among children. This study aims to explore how teacher competencies are implemented during the teaching and learning process in elementary schools. The research took place on Friday, June 14, 2024, at SD N Guwosari, located in Kembanggede, Guwosari, Pajangan, Bantul, DI Yogyakarta. The focus of this study is to highlight the essential role of teacher competence in classroom activities. A descriptive qualitative approach was applied, with data analysis following the Miles and Huberman model, which includes: (1) data collection, (2) data display, (3) data reduction, and (4) verification or conclusion drawing. The findings reveal that teacher competence holds a significant influence on the effectiveness of teaching and learning processes in elementary schools.